2022
DOI: 10.1021/acs.jafc.2c05954
|View full text |Cite
|
Sign up to set email alerts
|

Avicularin Alleviates Osteoporosis in Ovariectomized Mice by Inhibiting Osteoclastogenesis through NF-κB Pathway Inhibition

Abstract: Osteoporosis (OP) is mainly manifested by bone loss and bone degeneration. OP is considered a risk factor for pathological fractures, as well as impacts the health of middle-aged and elderly individuals. Drug therapy remains the main treatment scheme for OP; however, its efficacy is limited and has been associated with serious side effects. Therefore, it is important to develop new, effective, and safe treatment methods for OP. Avicularin (AL) is a flavonoid and quercetin derivative from various plants. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In RANKL knockout mice [ 43 ], NF-κB can promote osteoclastogenesis by activating the RANKL/RANK pathway [ 44 ]. Blocking NF-κB signaling is thought to be an effective way to prevent osteoclast activity [ 21 , 22 , 45 ]. Nrf2 is a redox-sensitive transcription factor that controls cellular antioxidant defenses by inducing antioxidant gene expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In RANKL knockout mice [ 43 ], NF-κB can promote osteoclastogenesis by activating the RANKL/RANK pathway [ 44 ]. Blocking NF-κB signaling is thought to be an effective way to prevent osteoclast activity [ 21 , 22 , 45 ]. Nrf2 is a redox-sensitive transcription factor that controls cellular antioxidant defenses by inducing antioxidant gene expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the OVX group and the OVX + Gar C group, respectively, an incision of about 1.5 cm in length was made in the middle of the lower abdomen of the mice under anesthesia and the incision was sutured after removing the bilateral ovaries and the surrounding adipose tissue. In the Sham group, only the ovaries were exposed, and the surrounding adipose tissue was removed and then incorporated into the abdominal suture to close the incision [ 21 ].The JONN laboratory in Suzhou, China, provided us with 24 experimental C57BL/6 mice (no. 202236274).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the signal transduction pathway of TLR4 can activate NF-κB continuously, thus promoting the transcription of various inflammatory factors and resulting in a cascade of inflammatory responses. NF-κB, a major transcription factor in inflammatory response, regulates the differentiation of both osteoblasts and osteoclasts and maintains bone homeostasis [ 31 ]. Our results showed that miR-137 significantly increased the protein expression levels of TLR4 and p65, which indicates that miR-137 may regulate osteogenic differentiation by activating the TLR4/NF-κB signaling pathway in hBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhu et al found that isopsoralen promoted the differentiation of human jawbone marrow mesenchymal cells into osteoblasts, suggesting its potential in restoring bone formation (Zhu et al 2023 ). Zhuang et al demonstrated that Avicularin (AL), a flavonoid and quercetin derivative, ameliorated osteoporosis by disrupting osteoclast formation through inhibiting the NF-κB pathway (Zhuang et al 2023 ). Huang et al discovered that dictamnine (DIC), a furoquinoline alkaloid, suppressed osteoclast formation, bone resorption, F-actin band formation, and osteoclast-specific gene expression by inhibiting the activity of nuclear factor erythroid2-related factor 2 (Nrf2), promoting the binding of Nrf2 and NF-κB, and blocking NFATc1 expression (Wong et al 2022 ).…”
Section: The Rankl/rank Signaling Pathway Activates Nfatc1mentioning
confidence: 99%